ELECTRICAL CHARACTERIZATION OF THE FORWARD CURRENTVOLTAGE OF AL IMPLANTED 4H-SIC PIN DIODES - MEGHERBI, M.L.; DEHIMI, L.; TERGHINI, W.; PEZZIMENTI, F.; DELLA CORTE, F.G. (Courrier du Savoir, 2015)
ABSTRACT In this work,theforward current-voltagecharacteristics of n-type Al implanted 4H-SiC pin diodeshave been investigated experimentally and by mean of numerical simulations in the 298-378K temperature range. Our simulations were performed using proprietary simulations software. The model parameters to be calibrated in the simulation are the electron and hole minority carriers lifetimes.The measured forward I-V characteristics showed two differentbehaviour, the leaky behaved and well behaved diode. The later diodes were considered for simulation comparison.Employing temperature-dependent carrier lifetimes as a fitting parameter, the simulation indicates that drift layer and bulk carrier lifetime ranging from 10ns to 50ns. We achieved a good agreement between simulations and measured data. The measured and the simulated forward characteristics indicate an ideality factor of about1.3for the region 2.5V-2.78Vand 2.14 in the low injection region. Activation energies of about 1.61eV and 2.51eVare obtained respectively which are in good agreement with the expected values. KEYWORDS: p-i-n diode, silicon carbide, silvaco, device simulation, lifetimes.